PENGARUH KEDISIPLINAN KERJA, KOMPETENSI, DAN PEMBERIAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT. AQUAFARM NUSANTARA SEMARANG - Joko Susanto, 12.05.51.0150; Rahayuningsih, Sri (Students Journal of Economic and Management, 2016)
This study analyzed the effect of work discipline, competence, and compensation awarding on employees performance. Object of study in this paper is the PT Aquarfarm Nusantara Semarang. The sampling technique in this research is to use simple random sampling (random) sample of 90 respondents as a data collection method using a questionnaire (questionnaire) by distributing a list of questions to the respondentin order to obtain information. The research objective wash formulated to determine the effect of work discipline, competence, and compensation awarding on employee performance. The data were analyzed using factor analysis to test the validity of the question items, Cronbach alpha formula to test the reliability of each of the independent variables were tested by regression analysis. The results of the research are : (1) work discipline has a positive and significant influence on imployee permormance. (2) competence has a positive and significant impact influence on imployee permormance. (3) compensation awarding has a positive and significant impact influence on employee performance Keywords : work discipline, Competence,Compensation Awarding, and Performance of Employees